Numerical and experimental investigations of low velocity impact on glass fiber-reinforced polyamide. (1st August 2018) - Mars, J.; Chebbi, E.; Wali, M.; Dammak, F.
Abstract: A numerical study was carried out to investigate the low velocity impact behavior of polyamide (PA) as matrix reinforced by a glass fiber. The assessment of the impact behavior requires tensile tests to determine the elastic-viscoplastic behavior of the composites. The numerical results are confirmed by experimental dropping weight impact tests. The material model is implemented in a user-defined material subroutine (UMAT) for the commercial finite element code ABAQUS to predict the numerical response of circular plate of glass fiber-reinforced polyamide subjected to low velocity impact. The effects of glass fiber volume fraction and incidental impact energy on the impact response of the composite circular plates are investigated. The impact analysis of the glass fiber-reinforced polyamide showed that the impactor velocity has considerable effects on the impact response of the composite plates. Also, the contact force changes proportionally with the impactor velocity. Highlights: Impact behaviors at low velocity of glass fiber-reinforced polyamide are investigated. User defined subroutine (UMAT) is developed and implemented in Abaqus. Experimental investigations of low velocity impact on glass fiber-reinforced polyamide. Finite element simulation in good agreement with experimental results.